2010
DOI: 10.1177/0010414009356176
|View full text |Cite
|
Sign up to set email alerts
|

Why Respecting Physical Integrity Rights Reduces Terrorism

Abstract: Does respect for human rights check or promote terrorism? This question is hotly debated within policy circles. Some hold that restricting human rights is a necessary if unfortunate cost of preventing terrorism. Others conclude that such abuses aggravate political grievances that contribute to terror. The authors demonstrate that theory and data support the latter position. They hypothesize that abuse of the subset of rights known as physical integrity rights fuels terrorism by making it more difficult for gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(137 citation statements)
references
References 42 publications
(59 reference statements)
5
132
0
Order By: Relevance
“…Countries with internal conflicts experience and produce more terrorism than other countries (e.g., Campos and Gassebner 2009;Piazza 2007;2008a;). The evidence for interstate conflicts and wars points in the same direction although the evidence is somewhat weaker (e.g., Braithwaite and Li 2007;Dreher and Fischer 2010;Koch and Cranmer 2007;Piazza 2008a;Walsh and Piazza 2010).…”
Section: Introductionmentioning
confidence: 92%
“…Countries with internal conflicts experience and produce more terrorism than other countries (e.g., Campos and Gassebner 2009;Piazza 2007;2008a;). The evidence for interstate conflicts and wars points in the same direction although the evidence is somewhat weaker (e.g., Braithwaite and Li 2007;Dreher and Fischer 2010;Koch and Cranmer 2007;Piazza 2008a;Walsh and Piazza 2010).…”
Section: Introductionmentioning
confidence: 92%
“…They find that terrorism is positively related to poor institutions such as a deficient rule of law (e.g., Choi 2010;Walsh andPiazza 2011), socioeconomic underdevelopment (e.g., Blomberg andHess 2008;Freytag et al 2011) and inefficient means of redistribution and economic participation (e.g., Burgoon 2006;Meierrieks 2010, Piazza 2011). If education positively interacts with economic and political development, as the previous discussion suggests, then education ought to be negatively related to terrorism since it removes the economic and institutional grievances that usually fuel terrorism.…”
Section: Hypothesis 1: Countries With Higher Levels Of Education Willmentioning
confidence: 99%
“…The source for political participation is the participation indicator of the Vanhanen Index of Democratization, compiled and made available in the Quality of Government database (Teorell et al 2011) while GINI is derived from the United Nations Development Program's World Development Report. Walsh and Piazza (2010) found that regimes characterized by physical integrity rights violations-abuses of the basic human rights of their citizens-experienced significantly higher rates of terrorism while Piazza (2008) found that regimes plagued by state failures both experienced and produced more transnational terrorism. I control for these in the models as well.…”
Section: Operationalizing Illicit Drug Markets and Counternarcotics Smentioning
confidence: 99%